2016
DOI: 10.1016/j.apcatb.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of bio-oil from biomass pyrolysis over Cu-modified β-zeolite catalyst with high selectivity and stability

Abstract: Upgrading of bio-oil from biomass pyrolysis over Cu-modified -zeolite catalyst in a down-draft fixed-bed reactor, in which the pyrolysis and upgrading processes are integrated, is investigated in details. It is found that high silica -zeolite has high selectivity to the hydrocarbon during the upgrading process. When it is modified by a small amount of Cu, the selectivity can be obviously promoted. Especially, when 0.50 wt% of Cu is loaded on it, almost only hydrocarbons can be detected in the light oil of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…Interestingly, loading of Cu and Mg on b-zeolite resulted in the obvious increase in specific surface area and pore volume when compared with the parent bzeolite. [12] However, hysteresis characteristic appeared after metal loading, suggesting that mesoporous structure was generated. This result is different from those reported ones, in which the surface area and pore size were always decreased by metal loading due to the metal sintering and/or the pore blocking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, loading of Cu and Mg on b-zeolite resulted in the obvious increase in specific surface area and pore volume when compared with the parent bzeolite. [12] However, hysteresis characteristic appeared after metal loading, suggesting that mesoporous structure was generated. This result is different from those reported ones, in which the surface area and pore size were always decreased by metal loading due to the metal sintering and/or the pore blocking.…”
Section: Resultsmentioning
confidence: 99%
“…The results are also shown in Table S2. [12] Then, further increase in Cu loading amount resulted in the obvious reduction of CH 4 and olefins yields due to the promotion of aromatization and alkylation reactions. This should be the contribution of copper species, which can be exchanged with the protons of Brønsted acid sites, resulting in the obvious increase of Lewis acid site amount.…”
Section: Resultsmentioning
confidence: 99%
“…Low concentration Cu-modified β-zeolite (0.5 wt%) increased selectivity to hydrocarbons during catalytic upgrading of Japanese knotweed pyrolysis bio-oil at 600 • C when compared to β-zeolite alone. It also decreased the coke deposition on Cu/β-zeolite catalyst [50]. Nickel substituted HZSM-5 catalyst improved hydrocarbon yield (around 16 wt%) and reduced coke yield during catalytic upgrading of aspen wood pyrolysis bio-oil vapor at 600 • C when compared to HZSM-5 alone [51].…”
Section: Reducing Catalyst Deactivation In Catalytic Crackingmentioning
confidence: 95%
“…It was found that catalysts prepared by the cyclodextrin-assisted co-impregnation method were more active than the materials synthesized via impregnation. In contrast to the previous work [39], a relatively high amount of Cu was incorporated into the structure of mesoporous materials (the highest efficiency of the hydrocarbons production was achieved for the samples containing 20% of Cu). In spite of a slightly lower acidity and surface area, the Cu/KIT-6 catalyst was more active in the formation of monocyclic aromatic compounds than the Cu/MCM-41 sample.…”
Section: Modification Of Zeolites and Mesoporous Materials By The Addmentioning
confidence: 67%
“…Widayatno et al [39] applied to this process a Cu-modified β-zeolite catalyst (containing up to 3% metal). The performed investigations revealed that the presence of copper also promoted the production of hydrocarbons; however, it was impossible to avoid coke formation during the upgrading process.…”
Section: Modification Of Zeolites and Mesoporous Materials By The Addmentioning
confidence: 99%